2023
DOI: 10.1093/jbcr/irad006
|View full text |Cite
|
Sign up to set email alerts
|

Alginate and Nanocellulose Dressings With Extract From Salmon Roe Reduce Inflammation and Accelerate Healing of Porcine Burn Wounds

Abstract: Partial thickness thermal burn wounds are characterized by prolonged inflammatory response, oxidative stress, tissue damage, and secondary necrosis. An optimal dressing for burn wounds would reduce inflammation and oxidative stress while providing a moist, absorbent, and protective cover. We have developed an extract from unfertilized salmon roe containing components with potential anti-inflammatory and antioxidative properties, called HTX. HTX has been combined with alginate from brown algae and nanocellulose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…The extract of Collex was found non-cytotoxic when evaluated according to ISO 10993-5:2009. Results from a minipig trial [ 37 ] suggest that Collex has significant potential to improve healing of burn wounds and motivates further clinical testing of Collex in the healing of burns and chronic hard-to-heal wounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extract of Collex was found non-cytotoxic when evaluated according to ISO 10993-5:2009. Results from a minipig trial [ 37 ] suggest that Collex has significant potential to improve healing of burn wounds and motivates further clinical testing of Collex in the healing of burns and chronic hard-to-heal wounds.…”
Section: Resultsmentioning
confidence: 99%
“…This work combines renewable, all-marine-sourced products to create a 3D printed wound dressing, referred to as Collex™, developed for the healing of hard-to-heal wounds, such as chronic wounds and burns, which are both low on exudate. The product developed herein was evaluated in parallel on porcine burn wounds, which indicated that Collex is a potent dressing for the treatment of burn wounds [ 37 ]. The work presented herein describes the ink optimization process and characterization of the material properties of this new wound healing dressing, which includes in vitro assays to determine cytotoxicity, the release profile of HTX, and its effect on human fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the defined inflammatory phase begins 24–48 h after the wound formation [ 37 , 40 ]. During this period, inflammatory mediators and chemokines related to the assembly and differentiation of leukocyte, lymphocyte and monocyte would increase sharply [ 41 , 42 ]. With the enrichment of these cells and chemokines, the proliferation of fibroblasts and endothelial cells begins in earnest.…”
Section: Woundmentioning
confidence: 99%
“…Nanocellulose-based composite dressings for burn wound healing. [200][201][202] Drug delivery systems 1. Nanocellulose-based carrier system for delivering anticancer drugs.…”
Section: Biomedical Application Recent Studymentioning
confidence: 99%
“…Nanocellulose‐based hydrogel dressings for chronic wound healing 198,199 Nanocellulose‐based composite dressings for burn wound healing 200–202 …”
Section: Nanocellulose In Advancing Bone Tissue Engineeringmentioning
confidence: 99%